3D carbon aerogel-supported PtNi intermetallic nanoparticles with high metal loading as a durable oxygen reduction electrocatalyst. (26th October 2017) - Wang, Yameng; Zou, Liangliang; Huang, Qinghong; Zou, Zhiqing; Yang, Hui
Abstract: Highly active and cost-effective oxygen reduction reaction (ORR) catalysts that have high metal loading and enhanced durability are desirable for the practical application in direct methanol fuel cells. Here, the preparation of a three dimensional (3D) carbon-based aerogel (CA) composed of graphene and multi-walled carbon nanotubes is reported and used as a support for an ordered PtNi intermetallic catalyst (OPtNi/CA) with a metal loading of 80 wt%. X-ray diffraction and transmission electron microscopic measurements confirm the formation of highly dispersed ordered PtNi intermetallic nanoparticles with a mean particle size of ca. 15.0 ± 1.0 nm. The as-prepared catalyst exhibits enhanced activity and durability for the ORR when compared to the Pt/C catalyst from BASF. The mass and specific activities of the ORR at 0.90 V on OPtNi/CA is ca. 1.4 and 1.8 times higher, respectively, than that using the commercial Pt/C catalyst. After an accelerated stress test, the mean particle size of the OPtNi/CA catalyst nearly kept unchanged. Both the improved activity and durability of the OPtNi/CA catalyst could be ascribed to the formation of an intermetallic compound, the uniform dispersion of PtNi nanoparticles, and the 3 D structure of the support. Highlights: 3D carbon aerogel-supported PtNi intermetallic nanoparticle is prepared. The catalyst exhibits much enhanced activity and durability for the ORR. The size and intermetallic structure nearly keep unchangeable under durability test.